Hubungan antara Kepuasan Kerja dengan Perilaku Kewargaorganisasian (PKO) Guru di SMSK Negeri Kecamatan Pasar Minggu Kota Administrasi Jakarta Selatan - Dwi Sakti Nugroho; Sutjipto Sutjipto; Matin Matin (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2017)
This study aims to know there is a relationship between job satisfaction with teacher OCB at Vocational High School Pasar Minggu, South Jakarta Administration. This research use quantitative with two variables there in, namely: (X) job satisfaction as independent variables and (Y) OCB as the dependent variable. The method used is survey method with the results of the analysis of correlational studies. The population in this study are teacher’s at vocational high school in Pasar Minggu, South Jakarta there is 275 teachers. Samples were taken by using simple random sampling technique. The technique is based on the sample size used in this study as many as 73 teachers. Data collection for the variable (X) job satisfaction and variable (Y) OCB using a questionnaire. Hypothesis testing is done using product moment correlation formula in can correlation coefficient (r) = 0,45283 and based on the results of hypothesis testing using t-test obtained t for 4.280 > 1.994 t-table. From this research, we get there’s positive relation between job satisfaction with OCB at Vocational High School Pasar Minggu, South Jakarta Administration. The contributions made by teachers job satisfaction on OCB, amounted to 20.51%.